Clinical Significance of Urine Heparanase in Bladder Cancer Progression - Itay Shafat (Neoplasia: An International Journal for Oncology Research, 2008)
Heparanase is an endo-β-glucuronidase capable of cleaving heparan sulfate (HS), an activity implicated in tumor metastasis. Heparanase expression is upregulated in primary human tumors, correlating with reduced post operative survival and elevated microvessel density. An ELISA method was used to quantify heparanase in urine from 282 individuals. Urine was collected from healthy volunteers (n = 41), patients diagnosed with noncancerous pathologic disorders (n = 90), and bladder cancer patients (n = 92). Fifty-nine bladder carcinoma patients after transurethral resection (TUR) with no evidence of disease (NED) were also included. Heparanase levels were significantly elevated in urine from bladder cancer patients compared with healthy controls (P < .001) and with noncancerous urinary disorders (P < .05). Heparanase elevation strongly correlated with tumor grade (P < .001) and stage (P = .027). An optimal cutoff value of 154 pg/ml was determined. Of 199 individuals enrolled (59 patients after TUR and 24 patients with recurring disease were excluded), 65 had heparanase levels above 154 pg/ml. Only 3 of 65 (4.6%) were healthy individuals. In contrast, 52.3% (34 of 65) of individuals with heparanase levels above 154 pg/ml were bladder cancer patients. The results indicate that urine heparanase levels are elevated during bladder cancer progression, suggesting that the ELISA method may be applied for bladder cancer diagnosis.